Three Dimensional Space-Time Analysis Theory of Geotechnical Seismic Engineering - Yang, Changwei; Yang, Guotao; Zhang, Jianjing; Ma, Hongsheng; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
Written by respected experts, this book presents essential findings on the Wenchuan earthquake. It establishes a series of time-frequency analysis methods, and subsequently applies them to the layered site, slope, and earth-retaining wall. Further, it examines various cases and their solutions, and shares the results of numerous shaking-table tests and numerical simulations. As such, it is a valuable resource for researchers and engineers in the fields of geotechnical engineering and anti-seismic engineering.
Basis of Seismology -- Analysis Technics of Seismic Signals -- Analysis of Seismic Dynamic Characteristics of High and Steep Rock Slopes -- Time-frequency Analysis Theory of Seismic Stability of High and Steep Rock Slopes -- Time-frequency Analysis Theory of Seismic Stability of Retaining Structures -- Seismic Dynamic Time Frequency Theory of Layered Site.
Keywords: Engineering geology; Geotechnical engineering; Mechanics, Applied; Solids; Natural disasters; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Solid Mechanics; Natural Hazards